Comparative Effect Of Fish Oil And Niacin Supplementation In Lowering Lipid Profile In Dyslipidemic Patients - Qaisar Raza , Kinza Imran, Bakhtawar Majeed , Zonaira Nasir , Kanza Fatima , Kainat Shehzad (Migration Letters, 2024)
Fish oil and Niacin supplementation, both have shown to have potential in correcting lipid profile in dyslipidemic patients which is associated as an important [1]risk factor for developing cardiovascular disease. In this study we evaluated the effect of fish oil capsule and niacin supplementation in correcting lipid profile (reducing serum triglyceride, total cholesterol, LDL, and increasing HDL) separately and in comparison to each other in confirmed dyslipidemic patients. Total 90 dyslipidemic patients both male and female were included and were further divided into 3 groups of 30 participants in each group. Group A was taken as control group, group B was given fish oil supplementation 1g twice daily and group C was given extended release niacin 500mg/day for 2 months. Fasting serum lipid profile test was taken and recorded at initial (0 day), post 1 (30th day) and post 2 (60th day) to see any significant effect. Serum samples of each individuals was analyzed at different hospitals and clinics in two major cities of Pakistan namely of Lahore and Layyah and statistically evaluated as any significant difference among the groups. After analyzing the mean difference between three groups, it can be seen that group II (fish oil) had shown significant effect(p<0.05) in reducing total cholesterol level, LDL level and triglyceride level, whereas group III (niacin) had shown significant effect (p<0.05) in increasing HDL level as compared to other groups from 0 day till 60th day. We concluded that fish oil can be used if the goal is to reduce serum LDL level, triglyceride level and total cholesterol level whereas, if the goal is to increase HDL only then better choice could be Niacin as it has better effectin increasing HDL level more than fish oil capsule.